1997
DOI: 10.1046/j.1365-2435.1997.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off between height growth and stem diameter growth for an evergreen Oak, Quercus glauca, in a mixed hardwood forest

Abstract: Summary 1.Patterns of stem growth of a mid-successional evergreen Oak species (Quercus glauca) in a mixed hardwood forest were examined to explore the trade-off relationship between stem-diameter growth and height growth. 2. The mean cross-sectional area (and the corresponding mean diameter) of a stem at a point in time was defined as the stem volume divided by tree height. Based on this definition, a simple equation representing the trade-off relationship between the height growth and mean diameter growth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 27 publications
3
32
0
2
Order By: Relevance
“…They thus do not account for variation in growth rates or allometries among individuals (Clark, 2010) and over a tree's life-span, due to, for example, variation in the relationship between height and diameter growth rates between dominant and suppressed trees (Sumida et al, 1997) or temporal autocorrelation of growth rates (Kohyama et al, 2005). Nevertheless, as a tool used to examine mean differences in tree growth and form between soil habitats, our models provide insight into the competitive strategies that tree species exhibit along resource gradients.…”
Section: Allometric Growth Modelsmentioning
confidence: 99%
“…They thus do not account for variation in growth rates or allometries among individuals (Clark, 2010) and over a tree's life-span, due to, for example, variation in the relationship between height and diameter growth rates between dominant and suppressed trees (Sumida et al, 1997) or temporal autocorrelation of growth rates (Kohyama et al, 2005). Nevertheless, as a tool used to examine mean differences in tree growth and form between soil habitats, our models provide insight into the competitive strategies that tree species exhibit along resource gradients.…”
Section: Allometric Growth Modelsmentioning
confidence: 99%
“…On the other hand, it can be straightforwardly evidenced that to neglect Δh/h in eqn. 4, as e.g., carried out in the professional practice by adopting the so-called K400 criterion (see (Sumida et al 1997): under natural conditions, a decrease of the longitudinal growth with size can be observed for most tree species, while radial growth tends to be constant for long time (Hara et al 1991). Although age influence cannot be completely excluded, various authors (e.g., Maggs 1964in Enquist 2003, Mencuccini et al 2005, Anfodillo et al 2006, Petit et al 2008 have shown that the reduction of height increment is mainly due to functional tree-size constraints: from a practical point of view, small trees tend to have greater relative height increments regardless of age, while large trees tend to have gradually smaller relative ones.…”
Section: Discussionmentioning
confidence: 99%
“…Despite spatial and temporal variability of the light conditions of branches, the measurement of relative PPFDs on overcast conditions has been accepted as a method to conveniently assess the light conditions of branches [48][49][50][51][52][53]. However, the growth and longevity of branches would be influenced by stand density, inter-tree competition [54][55][56], plant hormones [57], and programmed cell death [58].…”
Section: Branch Autonomy Versus Correlative Inhibitionmentioning
confidence: 99%